2021
DOI: 10.3390/jcm10112480
|View full text |Cite
|
Sign up to set email alerts
|

Monitoring of Changes in Masticatory Muscle Stiffness after Gum Chewing Using Shear Wave Elastography

Abstract: This study aimed to investigate if intensive exercise affects the stiffness of the masticatory muscles measured with shear-wave elastography. The study included a cohort of healthy adults (n = 40) aged 40 ± 11 years. In each individual, the stiffness of both the masseter and temporalis muscle was examined three times: at baseline, after 10 min of intensive exercise (chewing gum), and after 10 min of relaxation. Stiffness values (median (IQR)) of both the masseter and temporalis muscle were the lowest at the ba… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

1
10
1

Year Published

2021
2021
2023
2023

Publication Types

Select...
6

Relationship

3
3

Authors

Journals

citations
Cited by 9 publications
(14 citation statements)
references
References 24 publications
1
10
1
Order By: Relevance
“…The effect of age on stiffness has been reported in the literature for other muscles but not for the masseter muscle. Ekby et al [18] examined the stiffness of biceps brachii in a group of 133 healthy subjects and reported similar findings to our study. They found that shear modulus values increased with age in full extension of the muscle, especially in people over 60 years of age.…”
Section: Discussionsupporting
confidence: 90%
See 2 more Smart Citations
“…The effect of age on stiffness has been reported in the literature for other muscles but not for the masseter muscle. Ekby et al [18] examined the stiffness of biceps brachii in a group of 133 healthy subjects and reported similar findings to our study. They found that shear modulus values increased with age in full extension of the muscle, especially in people over 60 years of age.…”
Section: Discussionsupporting
confidence: 90%
“…We analyzed data obtained from 140 healthy volunteers (74 men and 66 women) with a median age of 50 years (95% confidence interval (CI): 45.9-55). For women, the median The stiffness of the masseter muscle was measured with the Aixplorer Ultimate device (SuperSonic Imagine, Aix-en-Provence, France) using a high-frequency linear probe SL 18-5 (5)(6)(7)(8)(9)(10)(11)(12)(13)(14)(15)(16)(17)(18). The obtained measurements were validated using the elasticity QA Phantom model 049A (Computerized Imaging Reference Systems, Inc, Norfolk, VA, USA).…”
Section: Resultsmentioning
confidence: 99%
See 1 more Smart Citation
“…For this reason, there is a need to characterize each of the muscles separately and provide values for the healthy muscle and each pathological condition individually. There is also a need to investigate factors influencing muscle stiffness such as age, treatments or exercise because such factors were proved to change masseter muscle stiffness in adults [34,35].…”
Section: Discussionmentioning
confidence: 99%
“…The results of shear wave elastography were proved reliable and reproducible [ 17 , 18 ]. Furthermore, the literature reports suggest that this tool is reliable in measuring the changes in stiffness of the masseter muscle in response to physical therapy (namely massage) [ 19 , 20 ] and exercise [ 21 ], both of which may be used in TMD management. However, there is little evidence on the use of shear wave elastography to evaluate treatment effects in patients undergoing conservative treatment for masticatory muscle disorders.…”
Section: Introductionmentioning
confidence: 99%